ALIHFUNGSI LAHAN MENGUBAH WAJAH DESA - Gerald Noveriano Leonis (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2019)
Village is an important social unit in the living space that also experiences its dynamics. In contrast to cities, villages give us perspective on value and historical construction. With the development and uncontrolled population explosion also has an impact on the changing face of the village. The crowded city forced the population to migrate to find land in the village. This study aims to interpret changes in the face of the village as a result of urban migration. This study uses qualitative methods with a case study approach. Data collection is done by interviews, observation and document study. This study took respondents from the initial community, migrants (city residents) who built residential in the village, as well as village apparatus. Based on the results of the study, there were a variety of impacts that occurred as a result of the migration of city residents to villages. Different residential buildings, better economic stability signal that there will be social inequality in the village, and this gives an impulse for social decohesiveness.